AN ANALYSIS OF STUDENTSâ SKILL IN WRITING DESCRIPTIVE PARAGRAPH AT GRADE X OF MA AL FATA PASIR AGUNG BANGUN PURBA - Indrayani, Leni; Sukma, Dian; Rahayu, Pipit (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research to describe the studentsâ skill in writing descriptive paragraph. This research wasdescriptive qualitative and used written test as instrument for collect the data. The result of this research inindicator content, students got scores with average 51,33% on fair. In indicator of organization, students gotscores with avarage 43,33% on fair. In indicator of vocabulary, students got scores with avarage 56,67% onfair and indicator grammar,students got scores with avarage 51,67% on fair. The result of all indicator was50,75% on the fair category. The conclusion of this research was on the fair category.